Técnica invasiva designada a la laparoscopia exploratoria de la cavidad abdominal en la especie canina - Betancourt, Julio; Toloza, Miller; Arcila , Victor (Spei Domus, 2005)
Invasive technique for exploratory laparoscopy in the abdominal cavity of dogs. Exploratory Laparoscopy is a minimally invasive diagnostic technique that can be used instead of exploratory (laparatomy) to explore the abdominal cavity, without having the associated effects of an open surgery such as long recovery, pain, and larger tissue manipulation. Laparoscopies were performed in 30 dogs (15 males). Ageranged 1.5 to 12 years and weight 5 to 25 Kg. All procedures were done under general anesthesia, and using a flexible fibrogastroscope. CO2was used to induce pneumoperitoneo. To develop the more appropriate technique that enable us the use of the flexible endoscope, three different surgical protocols to approach the abdominal cavity were tested. It was determined that for the use of flexible endoscope, intraumbilical incision was the most feasible protocol. Our observations indicate that this technique could be used to explore the ventral part of liver, stomach, spleen, and diaphragm. However, the exploration of descendent duodenum, descendent colon, kidney, pancreas, uterus, and ovaries is less feasible. Although this technique provides a general view of the abdominal cavity, it does not allow detailed organ examination.